Design Considerations for Storage and Content-Based Retrieval of Distributed Music Audio Objects - K. Nithya, P. Vidyadhari, P. Padmanabham, B. Vijayakumar (International Journal of Advanced Science and Technology, 2020)
Content based music audio retrieval system assists the users to retrieve the desired music audio objects from potentially large music repositories stored at various sites in a network. The framework discussed in this paper includes mechanisms for database creation, computation of cross correlation coefficients, site level index creation, similarity match and the retrieval process. The user from the query initiation site submits a music audio query clip as input. The framework returns the matched music audio objects along with their correlation values. The current work offers flexibility and scalability in terms of number of sites and users who mainly work on audio retrieval systems.